ОРГАНІЗАЦІЙНА ТА УПРАВЛІНСЬКА ОСНОВА КООПЕРАЦІЙ У СФЕРІ ІННОВАЦІЙ ТА ІНТЕЛЕКТУАЛЬНОЇ ПРАЦІ - Клевчік, Леонід; Антохов, Андрій (My University, 2021)
The article systematizes the organizational forms of cooperation in the field of innovation and intellectual work. Such forms are described in terms of commercial (IT companies; innovative enterprises; consulting agencies), cooperative (innovation centers; coworking centers; outsourcing companies, business incubators, industrial parks), virtual (freelance exchanges; IT, incu; crowdsourcing of the online platform;) and non-profit (research institutions, research and innovation centers; institutes of civil science, "Creative Commons"; "IT-House" networks). The organizational forms, priority in development for formation of technological and singular economic system of the Carpathian region at the local level are defined. The importance of coworking centers for the development of the organizational basis of cooperation in the field of innovation and intellectual work is substantiated. Organizational forms of cooperation in the field of innovation and intellectual work play a significant role in mobilizing intellectual potential aimed at realization in knowledge-intensive areas of the economy. The effectiveness of such forms depends on compliance with the principle of organization - individual and group performance with the provision of super-additive effect, the possibility of reaching higher levels of cooperation. It is noted that the development of technological-singular regional economic systems is based on the localization of innovation processes and the creation of cells of intellectual labor in the region. Depending on the specifics of the economy and the structure of employment, for different regions should be defined specific organizational forms of cooperation in the field of innovation and intellectual work. For regions where the IT sphere is actively developing and employment on a freelance basis is widespread, coworking centers are an actual form of development of local technological and singular systems. Their network is the optimal basis for strengthening technological and singular processes in the economy through organized interaction with other institutions.
Keywords: організаційні та управлінські форми кооперацій; інноваційна діяльність; макроекономіка; управління змінами; менеджмент; самоменеджмент; інтелектуальна власність